2008
DOI: 10.1186/1471-230x-8-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of constipation in Europe and Oceania: a systematic review

Abstract: Background: We aimed to review the literature regarding the epidemiology of constipation in Europe and Oceania and the associated prevalence/risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
242
3
27

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(292 citation statements)
references
References 40 publications
20
242
3
27
Order By: Relevance
“…Systematic reviews found a predominance of women and elderly people with CC 2, 3 and reported prevalence rates of 17.1% and 15.3% in Europe and Oceania, respectively 2. In an online survey of 5155 Japanese, 28.4% respondents self‐reported constipation 4.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews found a predominance of women and elderly people with CC 2, 3 and reported prevalence rates of 17.1% and 15.3% in Europe and Oceania, respectively 2. In an online survey of 5155 Japanese, 28.4% respondents self‐reported constipation 4.…”
Section: Introductionmentioning
confidence: 99%
“…Dados da América do Norte mostraram uma variação entre 2% e 27% na prevalência dessa doença 4,5,6 , e nos países da Europa e Oceania entre 5% e 35% 7 . No Brasil, não existem dados publicados de prevalência na população geral, visto que os estudos encontrados na literatura foram todos realizados em subgrupos, como lactentes 8 , adolescentes 9,10 e mulheres na menopausa 11 .…”
Section: Introductionunclassified
“…Constipation is one of the most common gastrointestinal complaints in Europe, with estimates of prevalence ranging from 5 to 35 % of the general population depending on the definition criteria used (57) . Definitions generally encompass aspects of defecation frequency with or without measures of stool consistency (57) .…”
Section: Gastrointestinal Healthmentioning
confidence: 99%